Pengaruh Kompensasi, Beban Kerja Dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Di Sub Bagian Kepegawaian Dan Keuangan Dinas Pertanian Provinsi Daerah Istimewa Yogyakarta - Nany Noor Kurniyati; Indah Fajar Yuliani (Jurnal Solusi, 2021)
In this study, the population was an employee in the Personnel and Finance Sub-Department of the Yogyakarta Provincial Agriculture Office of 30 people. The entire population is also sampled. The data retrieval method uses questionnaires and questionnaire assessments using the Likert scale. The analysis was carried out using multiple regression analysis and hypothesis testing. Multiple regression analysis in this study was Y = 1,284 + 0.714 x1 + 0.241 x2 + 0.269 x3. Based on the T test calculation is as follows: The influence of compensation shows a number of 2.149 and the significance level of 0.037, which means compensation significantly influences employee job satisfaction. The effect of workload shows t count of 0.870 and the significance level of 0.392, which means the workload has no effect on employee job satisfaction. The effect of work motivation shows t count of 2.149 and significance of 0.041, which means work motivation significantly influences employee satisfaction. Based on the F test calculation is as follows: the effect of compensation, workload and work motivation on employee job satisfaction shows f count of 4.545 and the significance level of 0.011, which means that compensation, workload and work motivation together have an effect on employee job satisfaction In the Personnel and Finance Sub-Department of the Provincial Agriculture Service of the Special Region of Yogyakarta. Keywords: Compensation, Workload, Work Motivation, Employee Job Satisfaction